Exploring the relationship between polymorphic (TG/CA)n repeats in intron 1 regions and gene expression - Zhang Wei; He Lijun; Liu Wanqing; Sun Chang; Ratain Mark J (Human Genomics, 2009)
Abstract The putative role of (TG/CA)n repeats in the regulation of transcription has recently been reported for several cancer- and disease-related genes, including the genes encoding the epidermal growth factor receptor (EGFR), hydroxysteroid (11-beta) dehydrogenase 2 (HSD11B2) and interferon-gamma (IFNG). These studies indicated a correlation between gene expression levels and the presence or length of (TG/CA)n repeats in their intron 1 regions. A genome-wide search for genes with similar features may provide evidence of whether these dinucleotide repeats represent a class of universal regulators of gene expression, which has recently begun to be investigated as a quantitative complex phenotype. Using a public database of simple repeats, we identified 330 genes containing potentially polymorphic long (TG/CA)n repeats (n ≥ 12) in their intron 1 regions. One known physiological pathway, the calcium signalling pathway, was found to be enriched among the genes containing long repeats. In addition, certain biological processes, such as cation transport, signal transduction and ion transport, were found to be enriched in these genes. Genotyping of the long repeats showed that the majority of these dinucleotide repeats were polymorphic in the HapMap CEU (Caucasians from Utah, USA) samples of northern and western European ancestry. Evidence for a significant association between these repeats and gene expression was not observed in the genes selected based on their expression profiles in the HapMap CEU samples. Our current findings, therefore, do not support a role for these repeats as a class of universal gene expression regulators. A more comprehensive evaluation of the relationship between these repeats and gene expression, potentially in other tissues, may be necessary to illustrate their roles in gene regulation in the future.